Hydro-mechanical modelling and analysis of multi-stage tunnel excavations using a smoothed excavation method. (July 2021) - Song, Fei; Rodriguez-Dono, Alfonso; Olivella, Sebastia
Abstract: The main objective of this article is to provide a general numerical approach for the hydro-mechanical (HM) modelling of tunnels excavated in saturated rock masses exhibiting plastic behaviour, considering a multi-stage excavation process. First, a new excavation method has been proposed and implemented in the software CODE_BRIGHT, based on the finite element method. In this method, the stresses in the excavation elements are reduced smoothly. As verification, the principle of uniqueness has been tested for multi-stage excavation. Then, numerical studies have been carried out to verify the advantages of the proposed excavation method in the numerical calculation, showing that the proposed method improves computational efficiency and mitigates convergence issues. Hence, this method can solve the usual numerical difficulties related to excavation problems and, therefore, it allows a more in-depth analysis of the HM behaviour of rock masses during tunnel excavation. Moreover, the results obtained in CODE_BRIGHT using the proposed method are compared with existing solutions for longitudinal deformation profiles (LDP), including elastic–plastic solutions for mechanical problems and elastic solutions for HM problems. Furthermore, this article presents the HM modelling of tunnels excavated in saturated rock masses, analysing the sensitivity of the LDP to the HM conditions and to the rock mass quality. Finally, based on a large amount of data obtained from numerical simulations, empirical solutions for the LDP of tunnels excavated in saturated rock masses –in a steady-state HM framework– have been obtained by fitting non-linear curves for the normalised radial displacements that occur ahead and behind the tunnel face. Hence, this article attempts to provide a convenient set of alternatives for the preliminary design of tunnels excavated in saturated rock masses.